2017
DOI: 10.3389/fimmu.2017.00599
|View full text |Cite
|
Sign up to set email alerts
|

The Research Progress on Intestinal Stem Cells and Its Relationship with Intestinal Microbiota

Abstract: The intestine is home to trillions of microorganisms, and the vast diversity within this gut microbiota exists in a balanced state to protect the intestinal mucosal barrier. Research into the association of the intestinal microbiota with health and disease (including diet, nutrition, obesity, inflammatory bowel disease, and cancer) continues to expand, with the field advancing at a rapid rate. Intestinal stem cells (ISCs) are the fundamental component of the mucosal barrier; they undergo continuous proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 103 publications
0
49
0
2
Order By: Relevance
“…Finally, if pharmacological targeting of LGR5 proves to be non-viable, ineffective, too toxic, or expensive then perhaps other avenues for LGR5 targeting in CRC treatment could be pursued. There are a number of studies showing that dietary factors such as high fat, 88 curcumin, 89 vitamin D, 90 and alcohol, 91 along with alterations to the gut microbiota, 92 can affect both the frequency and tumourigenicity of LGR5 + cells, and LGR5 expression level. Such approaches to modulate LGR5 expression in tumour cells would be cost-effective if they could be proven to reduce CRC incidence or promote tumour regression.…”
Section: Targeting the Lgr5 Protein For Crc Treatmentmentioning
confidence: 99%
“…Finally, if pharmacological targeting of LGR5 proves to be non-viable, ineffective, too toxic, or expensive then perhaps other avenues for LGR5 targeting in CRC treatment could be pursued. There are a number of studies showing that dietary factors such as high fat, 88 curcumin, 89 vitamin D, 90 and alcohol, 91 along with alterations to the gut microbiota, 92 can affect both the frequency and tumourigenicity of LGR5 + cells, and LGR5 expression level. Such approaches to modulate LGR5 expression in tumour cells would be cost-effective if they could be proven to reduce CRC incidence or promote tumour regression.…”
Section: Targeting the Lgr5 Protein For Crc Treatmentmentioning
confidence: 99%
“…Reduced ISC Wnt/β‐catenin activity and decreased Wnt5a and Wnt11 expression were observed in mice lacking commensal bacteria . Several studies have also shown a clear link between Toll‐like receptor signaling by the microbiome and ISC Wnt signaling . Thus, an abnormal microbiome may disrupt ISC Wnt signaling required to maintain normal intestinal crypt cell fate and barrier function and may be a critical cause of inflammaging resulting in aging‐associated bone loss, as seen in the ovarectomized mouse model …”
Section: Wnt Signaling In Aging Intestinementioning
confidence: 99%
“…135 Several studies have also shown a clear link between Toll-like receptor signaling by the microbiome and ISC Wnt signaling. 136 Thus, an abnormal microbiome may disrupt ISC Wnt signaling required to maintain normal intestinal crypt cell fate and barrier function and may be a critical cause of inflammaging resulting in aging-associated bone loss, as seen in the ovarectomized mouse model. 121,137 As we have mentioned above, although genetic evidence has shown that LRP5 has crucial roles in regulating bone mass, the mechanisms by which LRP5 controls bone formation remain unclear.…”
Section: Wnt Signaling In Aging Intestinementioning
confidence: 99%
“…Various parameters (e.g. intestinal microbiota, intestinal metabolites, and cellular signaling pathways) regulate the proliferation and differentiation of intestinal stem cells, leading to the alteration in the number of each type of cells and the progression of various diseases like inflammatory bowel disease, infection, and cancer ( 7 , 9 15 ). Glutamine is a primary metabolic fuel of small intestinal enterocytes and is essential for the viability and growth of intestinal cells by serving as a precursor for synthesis of nucleotides, glucose, amino acids, and proteins ( 16 , 17 ).…”
mentioning
confidence: 99%